Compound parabolic concentrator design for red, green, blue, and white LED light mixing. (25th July 2016) - Wei, An-Chi; Lo, Shih-Chieh; Hung, Pei-Fang; Lee, Ju-Yi; Yeh, Hong-Yih; Huang, Hong-Cheng; Li, Chia-Ming
Abstract: A light-mixing module consisting of a compound parabolic concentrator (CPC) and a fiber for mixing light from red, green, blue, and white (RGBW) LEDs was proposed. The design principle was investigated and a design prototype was demonstrated in a simulation. The simulated results showed that the chromatic nonuniformity was reduced to 1/10 when the fiber length was 40 times the core width, and the module efficiencies were more than 80% and more than 60% when the fiber lengths were 350 mm and 5 m, respectively. The proposed module is suitable for solar lighting compensation or indoor lighting, such as plant-factory lighting.